Comparative analysis of diagnostic colonoscopy in symptomatic young adults from South Korea and the United States. Issue 35 (September 2017) - Kwak, Min Seob; Cha, Jae Myung; Byeon, Jeong-Sik; Lin, Otto S.; Kozarek, Richard A.
Abstract : Abstract: To date, not much is known about ethnic differences in the prevalence of colorectal neoplasia in symptomatic young patients with lower gastrointestinal symptoms. This study sought to compare diagnostic colonoscopic findings in symptomatic young patients from South Korea and the United States. Results from the first diagnostic colonoscopies in symptomatic 18- to 49-year-old patients were compared between the United States and Korean cohorts. The US cohort data were collected at Virginia Mason Medical Center in Seattle, Washington between January 2007 and January 2010, and the Korean cohort data were collected at 14 university hospitals in Korea between June 2006 and June 2015. The prevalence of advanced neoplasias was similar in both cohorts for bleeding and nonbleeding symptoms ( P = .966 and P = .076, respectively). In a subgroup analysis for 40- to 49-year-old patients, the prevalence of advanced neoplasias was similar for bleeding symptoms; however, nonbleeding symptoms were significantly higher in the Korean cohort than in the US cohort (6.2% vs 2.6%, P < .001). In an age subgroup analysis for 18- to 39-year-old patients, the prevalence of advanced neoplasias was similar for bleeding and nonbleeding symptoms in both cohorts. Multivariate analysis showed that lower gastrointestinal symptoms were not associated with the risk of any type of advanced neoplasia in young Korean patients. Ethnic disparities in the prevalence of advanced neoplasia on diagnostic colonoscopy were not noticeable between Korean and US young patients. However, 40- to 49-year-old patients with nonbleeding symptoms require more attention to detect advanced neoplasia in Korea than similarly aged patients in the United States.